Keberhasilan Mahasiswa dalam Penulisan Artikel Ilmiah: Studi Kasus Kelas Menulis FAH UIN Sunan Gunung Djati Bandung - Bunyamin Faisal; Fitriani Fitriani; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2024)
The research aims to discuss student success in writing scientific articles. This research uses a qualitative approach by applying descriptive-analytical methods. The results and discussion show that students achieved success seen from motivation, efforts made, and achievements in scientific article writing practice. This research concluded that the participants had demonstrated success in writing scientific articles even though the training was still ongoing.